Early Metoprolol Administration before Primary Percutaneous Coronary Intervention (PCI) in ST-Segment Elevation Myocardial Infarction: Impact on Left Ventricular Ejection Fraction - Amin, Muhammad; Nawaz, Tariq; Hussain, Sadam; Nayab Ali, Syed Muhammad; Hayat, Faisal Saleh (Biological and Clinical Sciences Research Journal, 2025)
Ischemic heart disease is the main cause of death globally, with STEMI being its most severe sign. Beta-blocker lower systemic blood pressure, heart rate, decreases ischemia damage when given before PPCI, particularly when metoprolol is used. Objective: the aim of this study was to find out the effect of early metoprolol administration before Primary Percutaneous Coronary Intervention (PCI) in STEMI. Methods: The current Randomized Controlled Trial was carried out at the Department of Cardiology, Lady Reading Hospital, Peshawar from 1st February 2025 to 31st April after taking permission from the ethical committee of the institute. A total of 60 participants were included and divided in to two groups and each group had 30 individuals. All collected data was entered into a computerized database, and SPSS version 25.0 was used for data analysis. To compare the effectiveness of early metoprolol administration before PCI in ST-segment elevation myocardial infarction on LVEF, an independent sample t-test was used to compare the mean LVEF values between the treatment group and the control group. A p-value of <0.05 were considered statistically significant. Results: Over all 60 individuals participated in the current study. The LVEF of metoprolol group was substantially higher than the control group at one week, three months, and 6 months following PCI (P <0.05). Before starting therapy, the two groups' LVEFs did not differ significantly (P >0.05). The intravenous metoprolol group's LVEF was considerably greater than the control group's at one week, three months, and six months following PCI. The Intravenous Metoprolol group's 6 months overall incidence of MACE was noticeably lower than the control groups. Conclusion: The current study concluded that in individuals with ST-Segment Elevation Myocardial Infarction early metoprolol administration before Primary Percutaneous Coronary Intervention (PCI) in ST-Segment Elevation Myocardial Infarction increase left ventricular ejection, can improve heart rate regulation, lessen myocardial damage, and enhance cardiac function and lower the risk of serious adverse cardiac events.